PEMBUATAN GULA CAIR RENDAH KALORI DARI DAUN STEVIA (Stevia rebaudiana (Bertoni) Bertoni) SECARA EKSTRAKSI MENGGUNAKAN METODE INFUSA DENGAN PELARUT AIR: PEMBUATAN GULA CAIR RENDAH KALORI DARI DAUN STEVIA (Stevia rebaudiana (Bertoni) Bertoni) SECARA EKSTRAKSI MENGGUNAKAN METODE INFUSA DENGAN PELARUT AIR - Rina Nurhayatina; Esa Yolanda; Sukmawati (Jurnal Medika Farmaka, 2026)
In general, sweeteners consumed by Indonesian people are sucrose sweeteners derived from sugar cane and synthetic sweeteners. In the long term, both types of sweeteners can cause various diseases. Therefore, a natural alternative that is safe for health and has a high level of sweetness is sought. One alternative natural sweetener is stevia sweetener derived from the Stevia rebaudiana Bertoni plant. Stevia is a natural sweetener other than sugar cane sweetener with a sweetness level of 200-300 from sugar cane sucrose sugar. This study aims to determine the effect of the extraction formulation that produces the best extract characteristics. Stevia sugar production is carried out by extraction with the infusion method on dry stevia leaf powder and extracted using a water bath to increase the sample temperature to 50°C using water as a solvent. This study evaluated low-calorie liquid sugar from Stevia rebaudiana Bertoni leaves through hedonic tests, pH, and water content. The results showed the most preferred taste (64.36%), color (59.27%) and aroma (58.18%). The pH value of the preparation is 6, according to the standard (5–7). The average water content of stevia powder is 6.5% which can produce a liquid sugar preparation that meets the quality requirements, namely (<10%). Stevia liquid sugar has the potential to be a preferred and stable natural sweetener.